New Insights of Zn2+/Li+ Hybrid Aqueous Batteries. Issue 11 (28th September 2020) - Mainar, Aroa R.; Iruin, Elena; Blázquez, Jose Alberto
Abstract : The integration of energy storage systems into intermittent renewable energy sources in power grids ensures the continuity of the energy supply in a balanced and efficient way. Novel rechargeable zinc ion and zinc hybrid aqueous technologies constitute paradigmatic examples of promising alternative energy storage systems for large‐scale applications, due to their intrinsic low cost, environmental friendliness, safety, high power density, and ease of operation. This work evaluates the performance improvement of zinc/LiFePO4 and zinc/LiMn2 O4 batteries through the incorporation of an alternative chloride‐based electrolyte formulation inspired in Leclanché battery technology and also, in recently reported secondary zinc–air batteries. The use of this alternative electrolyte shows an increased working voltage and improves capacity retention for both zinc/LiFePO4 and zinc/LiMn2 O4 batteries. This work analyses for the first time the specific energy of zinc‐based hybrid aqueous batteries in a functional cell, by means of the incorporation of light zinc anode and Li + ‐based cathode which comprises superior active material loading. This approach demonstrates the feasibility of reversible zinc‐based hybrid aqueous batteries with more than 90 W h kg −1 Active materials as to 13 W h kg −1 Active materials of the baseline technology. Abstract : This work evaluates the improvement of zinc/LiFePO4 and zinc/LiMn2 O4 batteries through the incorporation of an alternative chloride‐based electrolyte. Increased active material loading of the most promising positive electrode is evaluated with light zinc anode to demonstrate the feasibility of the technology with more than 90 W h kg −1 Active materials .